Psychiatric and neurocognitive consequences of endogenous hypercortisolism. (29th April 2020) - Piasecka, M.; Papakokkinou, E.; Valassi, E.; Santos, A.; Webb, S. M.; de Vries, F.; Pereira, A. M.; Ragnarsson, O.
Abstract: Psychiatric and neurocognitive symptoms due to hypercortisolism were already described by Harvey Cushing in his original paper on patients with Cushing's syndrome (CS). Nowadays, it is well known that psychiatric and cognitive complaints are two of the most common, and most distressing, symptoms in patients with CS. Psychiatric symptoms are indeed a major clinical manifestation of CS. The most commonly observed psychiatric conditions are depression and anxiety, whilst mania and psychosis are less common. Several domains of cognitive function are impaired at diagnosis, including episodic and working memory, executive function and attention. Following treatment, one‐fourth of the patients still experience depressed mood, and the cognitive impairments are only partially restored. Consequently, quality of life in patients with CS is severely and persistently affected. Neuroimaging studies have also illustrated the deleterious effects of hypercortisolism on the brain by demonstrating reduced grey matter volumes and cortical thickness, altered resting‐state functional responses and during cognitive tasks, as well as widespread reduced white matter integrity, especially in structures important for cognitive function and emotional processing, both before and after successful abrogation of hypercortisolism. In this paper, we summarize the current knowledge on the psychiatric and neurocognitive consequences of hypercortisolism in patients with CS, both before, and after successful treatment. In addition, we review the structural and functional brain abnormalities associated with hypercortisolism and discuss the influence of these factors on quality of life. Abstract :